The Level of University of Tabuk Faculty Members' Practice of Participatory Action Research Skills to Improve Teaching Practices - Layla Falah Salem Alomrani (University of Science and Technology, Yemen, 2020)
The study aimed to identify the level of applying participatory action research (PAR) skills by a sample of faculty members at Tabuk University to improve teaching practices (TP), and to find out whether there were statistically differences at significance level (α ≤ 0.05) between the mean scores of the study sample assessment attributable to the variables: (Gender, academic level, qualification type, years of experience). To achieve this, the descriptive analytical method was used, whereby a questionnaire was administered to a sample consisting of (114) FMs at UT in the academic year 1440/1441 AH. The questionnaire consisting of (40) items, covering seven key skills. The results showed that the total assessment level of the practice of PAR skills to improve TP from the viewpoint of FMs showed a 'high' level of significance with a mean of about (3.78). Those skills were arranged according to the assessment level in a descending order as follows: (setting the PAR goal, reviewing the literature on research focus area, drawing results and conclusions, implementing the action plan (AP), designing the AP, defining the PAR focus area, and designing a future procedural AP). Also, there were no statistically differences at significance level (α ≤ 0.05) between the mean scores of participants' assessment attributable to: (gender, educational level, qualification type, years of experience). The study recommended supporting the development of AR skills among the FMs and motivating them to conduct this kind of studies along with academic studies. It was also recommended to conduct studies on the effectiveness of practicing PAR skills to improve the university education and learning process at the level of academic programs or study courses level, taking into account other variables.